2020
DOI: 10.1515/corrrev-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of erosion wears of Al–Mg–Si–Cu–SiC composite produced by the PM method

Abstract: Metal matrix composites are expanding their range every day due to their various industrial applications in manufacturing sectors, to attain high performance and favorable characteristics such as light weight, more excellent corrosion as well as wear resistance, high specific strength and high temperature-resistance than conventional materials. This study deals with analysis on erosion wear characteristic and corrosion behavior of newly-engineered aluminum metal–matrix composite (Al–0.5Si–0.5Mg–2.5Cu–5SiC) dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Aluminium metal matrix composites (AMMCs) fabricated using powder metallurgy are expanding their range due to their characteristics, such as high-temperature resistance, high specific strength and lightweight than conventional materials. Behera et al [ 6 ] fabricated an aluminium–metal–matrix-composite (Al–0.5Si–0.5Mg–2.5Cu–5SiC). They found that the incorporation of fine SiC particles into sintered matrix elements can improve erosive wear resistance by a factor of 200–300%.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium metal matrix composites (AMMCs) fabricated using powder metallurgy are expanding their range due to their characteristics, such as high-temperature resistance, high specific strength and lightweight than conventional materials. Behera et al [ 6 ] fabricated an aluminium–metal–matrix-composite (Al–0.5Si–0.5Mg–2.5Cu–5SiC). They found that the incorporation of fine SiC particles into sintered matrix elements can improve erosive wear resistance by a factor of 200–300%.…”
Section: Introductionmentioning
confidence: 99%
“…The development of materials engineering made it possible to replace steel and cast iron with aluminum alloys in several applications due to the introduction of reinforcement particles that are able to modify the microstructure and provide an increase in mechanical strength 14 . However, studies have shown that the machinability of these materials has multiple negative aspects, such as adhesion and abrasion 6 .…”
Section: Introductionmentioning
confidence: 99%
“…the mechanical properties of ammC can be modified to meet the requirements in various industrial applications using the appropriate combination of metal matrix, reinforcement, and processing methods. the production process of aluminum composites was obtained using the powder metallurgy technique [1][2][3][4][5] and tested in terms of erosive wear in this work. a "sandblasting" type erosion device is used, in which sand particles hit a fixed disc under the required pressure.…”
Section: Introductionmentioning
confidence: 99%